TRANSGENDER’S RIGHTS TO SPORT COMPETITIONS FOLLOWING THE NEW RECOMMENDATIONS OF THE INTERNATIONAL OLYMPIC COMMITTEE (2021) - Petrėnaitė, Daiva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The topic of human rights is taking on new relevant forms, especially when it comes to transgender rights. Their right to participate in sports has always been a subject of much debate. In November 2021 the International Olympic Committee adopted the new recommendations “Framework on Equity, Inclusion and Non-Discrimination on the Basis of Gender Identity and Intersex” on transgender people, which declared that each federation has to decide for itself when setting its own rules regarding the right of these people to participate in sports competitions. So, one thing is clear there is no common position on this issue. The article aims to reveal the practical aspects of such regulation regarding the possibilities and limitations of transgender participation in individual sports. The applied research methods are analysis of legal acts and other documents, review of articles and scientific literature, and qualitative comparative analysis. The research results showed that despite the principles specified in the Framework prohibiting discrimination, in practice these principles can be difficult to harmonize, especially if we speak about fair competition and equal opportunities.